Experimental studies on the effect of chlorpyrifos on rats VI . Population o f intestinal mast Cells and hypersensitivity - Mahmoud, Ghyath Salih; elhasade, Amal S. (Al-Mukhtar Journal of Sciences, 2010)
This study performed to investigate the effects of chlorpyrifos ( Insecticides ) on the population o f intestinal mast cells . Thus a total of 110 male rats were used and divided into four groups The first group was used as a control , the median lethal dose (LD50) was determined according to Aldersy 2005, and appeared to be equal to 81.2 mg/Kg.B.W. While the second group of rats received an oral daily doses of 1/10 LD50. The third and fourth groups of rats were administered a single oral dose of 1/10 and 1/30 LD50 respectively . The mast cells were recognized with their specific morphological characters in the intestinal mucosa, submucosa and muscularis ,under the influence of chlorpyrifos adminstration. A comparative and statistical investigations revealed a marked degranulation and increase in the population of mast cells in the intestinal layers of experimental rats, compared with the rats of the controlled group.